The Black body in ecstasy: reading race, reading pornography - Nash, Jennifer C. (Duke University Press, 2014)
In The Black Body in Ecstasy, Jennifer C. Nash rewrites black feminism's theory of representation. Her analysis moves beyond black feminism's preoccupation with injury and recovery to consider how racial fictions can create a space of agency and even pleasure for black female subjects. Nash's innovative readings of hardcore pornographic films from the 1970s and 1980s develop a new method of analyzing racialized pornography that focuses on black women's pleasures in blackness: delights in toying with and subverting blackness, moments of racialized excitement, deliberate enactments of hyperbolic blackness, and humorous performances of blackness that poke fun at the fantastical project of race. Drawing on feminist and queer theory, critical race theory, and media studies, Nash creates a new black feminist interpretative practice, one attentive to the messy contradictions—between delight and discomfort, between desire and degradation—at the heart of black pleasures.
Section: x, 219 p. : ill. ; 23 cm.
Keywords: 1900-1999; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; féminisme afroaméricain; féminisme pop; lit4700; pornographie; premier cycle; périodes historiques; queer; régions géographiques; sexualité; thématiques; états-unis; études culturelles

Chap. 1 Les langages du sexe. - Weeks, Jeffrey; Mendès-Leite, Rommel; Collomb-Boureau, Colette; Millet, Baudoin; Baudry, Samuel (Sexualité, 2014)
Première traduction française d'un ouvrage de Jeffrey Weeks, ce "manifeste intellectuel" est d'ores et déjà un classique anglo-saxon depuis plus de vingt ans. Dès sa première édition, il s'est imposé comme une introduction de pointe aux débats sur les sexualités, le genre et l'intime. Jeffrey Weeks retrace 1'histoire de sexualité pensée comme une construction sociale, façonnée et remodelée inlassablement par le contexte dans lequel elle existe et s'exprime : la sexualité n'est ni naturelle ni uniforme, mais culturelle et plurielle. Cette approche pionnière permet de couvrir un grand champ d'investigation : les traditions religieuses, les politiques identitaires, la mondialisation, l'impact social du sida, l'influence de la génétique et de la psychanalyse, la lutte des sexes, les nouveaux modèles familiaux... Désormais, dans sa troisième édition (qui fait l'objet de cette traduction), cet essai majeur intègre de nouveaux concepts et enjeux, en particulier des mouvements LGBT et des débats sur le mariage homosexuel.
Section: 1 vol. (303 p.) : couv. ill. en coul. ; 18 cm.
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; angleterre; approches et analyses; cours; discipline; discours dominant; europe; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques